What Diet, Physical Activity and Behavioral Strategies Are Used by Women with Polycystic Ovary Syndrome and Where Are They Sourced From?. (7th June 2021) - Cowan, Stephanie; Grassi, Angela; Couch, Lynn; Jeanes, Yvonne; Lim, Siew; Pirotta, Stephanie; Moran, Lisa
Abstract: Objectives: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting 13% of reproductive-aged women. Lifestyle management is the first-line treatment for improving reproductive, metabolic and psychological complications in PCOS, however women experience challenges with implementing behavioral change. This indicates a clear need to better understand how women with PCOS engage with evidence-based dietary and physical activity (PA) interventions. The primary aim of this study was to identify the types and sources of dietary and PA interventions implemented by women with PCOS. A secondary aim was to understand how they use behavioral and cognitive self-management strategies to support behavioral change. Methods: In this cross-sectional study an online questionnaire was disseminated via the PCOS Nutrition Centre (a consumer-based website) between May 2015-May 2016. Women ( n  = 1167) were aged 18–45 years, primarily born within the United States (70%) and self-reported a PCOS diagnosis. Results: While only 33% and 16% of women reported following formal nutrition or PA guidelines (respectively), 57% had implemented a 'special diet' to help manage their PCOS. Many of these diets were not supported by evidence-based PCOS practice. Participants also displayed a low level of engagement with important self-management behaviors, including goal setting and positive self-talk. The internet was the primary source of nutrition (36%) and PA (32%) information, with few turning to health professionals including doctors (nutrition 16%; PA 13%) and dietitians (nutrition 4.8%; PA 2.4%). Conclusions: These findings suggest that online information may promote inaccurate non-evidence-based lifestyle advice, and indicates a need to increase engagement with qualified health professionals. As current lifestyle advice for PCOS management utilized by health professionals are based on generic national guidelines, it is possible that this one-size-fits-all approach does not satisfy their desire for more personalized recommendations. It is also likely that health professionals will need to diversify their mode of communication through the delivery of online lifestyle education. Funding Sources: This research received funding from the National Heart Foundation of Australia and the National Health and Medical Research Council.